Responsible behavior of the 100 companies with highest income in Ecuador - Aguilar Viteri, Andrés (2023)
Moral responsibility is decisive in the development of business activities. This management channel achieves a positive act and maintains satisfactory relationships with the interested agents, which transcends the image and reputation of the companies, their behavior benefits the business environment and society. The type of research is qualitative based on the methods of content analysis that transcended the reflection initiated by the data collection, which experienced an unforeseen turn by the Covid-19, however, it was carried out through documentary review such as the memories sustainability, risk rating reports, audit reports, Web content, among others for your study and understanding. 12 categories of responsible conduct were defined. The response scale is ordinal dichotomous; Kendall's coefficient of concordance was applied to the results obtained, being significant; also the Chi² in which it demonstrates that the data have a dependency relationship; and to measure its reliability consistency, it was carried out using Cronbach's Alpha, which is acceptable. To visualize and verify the level of associability between the level of income and the sector of companies with responsible behavior, the Multiple Correspondence Analysis -ANACOR was used. The results evidenced show that the responsible behavior of the 100 companies does not necessarily depend on the level of income, although there is a focus on the sector to which the companies belong, it is also concluded that the information reviewed is declarative and positive, although it is not necessarily a demonstration of fair treatment to its stakeholders but to improve its image and reputation. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/2186